Synthesis, Characterization and Biological Evaluation of Polymer Nano Dimetal Oxides Derived from Poly Methylmetha Acrylate and Y2O3 \ La2O3 Prepared in Green Method - Abd, Zainab Ahmed; Abbass , Nada Mutter (Iraqi Journal of Science, 2025)
In this work, metal oxides [Y2O3\La2O3] nanoparticles were synthesized using a green method with ashwagandha extract, which served as a reducing agent. This extract also catalyzed the polymerization of poly methylmetha acrylate, resulting in the formation of nanocomposites [PMMA\Y2O3\La2O3]. The morphology, size, and structures of the synthesized nanocomposites were determined and characterized using thermogravimetric analysis (TGA), x-ray diffraction (XRD), differential scanning calorimetry (DSC) analysis, and field emission scanning electron microscopy (FESEM), tested by antioxidant activity and antibacterial activity. To confirm the design of nanocomposites-based nanostructures and to reveal unique characteristics, the distribution of the nanoparticles within PMMA was analyzed determined. The results from AFM of the synthesized nanostructure of Y2O3 and La2O3, showed that the size of NPs was within the nanoscale range. The biological activities of synthesized nanocomposites were examined, including antioxidant and the use of these nanocomposites as inhibitors for bacteria. The findings demonstrated that the nanocomposites revealed they have a significant inhibitory effect.